Influence of functional food composition on the properties of meat mince systems - Strashynskyi, Igor; Fursik, Oksana; Pasichnyi, Vasyl; Marynin, Andriy; Goncharov, Georgi (My University, 2016)
In the technology of meat products, a promising direction research is the use of functional summaries shey For the improvement of minced meat systems of boiled kov- bass used the developed and researched functional a food composition containing a complex of proteins preparations with hydrocolloids. It was established that it was introduced addition to the composition of minced meat improves and stabilizes them functional-technological and structural-mechanical properties The obtained results prove the promising the ability to replace part of the meat raw material with a created one composition. У технології м’ясопродуктів перспективним напрям- ком досліджень є використання функціональних сумі- шей. Для удосконалення фаршевих систем варених ков- бас використали розроблену і досліджену функціональну харчову композицію, яка містить комплекс білкових препаратів з гідроколоїдами. Встановлено, що її внесен- ня до складу м’ясних фаршів покращує та стабілізує їх функціонально-технологічні та структурно-механічні властивості. Отримані результати доводять перспек- тивність заміни частини м’ясної сировини створеною композицією.
Keywords: кафедра технології м’яса і м’ясних продуктів; minced cooked sausages; protein-rich composition; functional and technological properties; effective viscosity; ultimate shear stress; фарші варених ковбас; білоквмісна композиція; функціонально-технологічні властивості; ефективна в’язкість; граничне напруження зсуву